Penerapan Konseling Kelompok untuk Meningkatkan Penyesuaian Diri pada Penyandang Disabilitas Fisik - Luthfiah Alin; Neni Noviza (Journal of Society Counseling, 2025)
This study aims to explore the self-adjustment of individuals with physical disabilities at Sentra Budi Perkasa Palembang and to examine how group counseling can be applied to improve their self-adjustment. A qualitative field-research approach was employed, with data collected through observation, group counseling sessions, in-depth interviews with a social worker and individuals with physical disabilities, and documentation review. The research subjects consisted of one social worker and five individuals with physical disabilities. Data were analyzed using data reduction, data display, and conclusion drawing/verification. The findings indicate that the subjects showed low levels of self-adjustment on the personal dimension, characterized by limited self-acceptance, difficulty in emotional regulation, and the absence of clear life goals, as well as on the social dimension, marked by limited interaction, low empathy, and minimal group participation. Group counseling was implemented through four stages—forming, transition, working, and termination—and proved effective in improving both the personal and social self-adjustment of individuals with physical disabilities. These findings support the growing body of evidence that structured, group-based psychosocial interventions are a viable strategy for supporting adjustment among individuals with disabilities.